Crystal orientation measurements using SEM–EBSD under unconventional conditions. Issue 2 (12th May 2015) - Kunze, Karsten
<x content-type="archive" xml:space="preserve">Abstract</x> Electron backscatter diffraction (EBSD) is a micro-analytical technique typically attached to a scanning electron microscope (SEM). The vast majority of EBSD measurements is applied to planar and polished surfaces of polycrystalline bulk specimen. In this paper, we present examples of using EBSD and energy-dispersive X-ray spectroscopy (EDX) to analyze specimens that are not flat, not planar, or not bulk – but pillars, needles, and rods. The benefits of low vacuum SEM operation to reduced drift problems are displayed. It is further demonstrated that small and thin specimens enhance the attainable spatial resolution for orientation mapping (by EBSD or transmission Kikuchi diffraction) as well as for element mapping (by EDX).